KEPEMIMPINAN INOVATIF KEPALA MADRASAH DALAM MENINGKATKAN DAYA SAING MADRASAH - Irma Hermawati; Kun Nurachadijat (Program Studi Pendidikan Agama Islam, Universitas Majalengka, 2023)
In every organization the position and role of the leader is always very central. The progress and decline of the organization is very dependent on the extent to which the leader is able to imagine advancing his organization. Likewise, in the context of the madrasa as an organization, the position of the head of the madrasa is also very important in advancing the institution he leads. An innovative leader is a leader who has a leadership style as a democratic style or a leadership style that does not make decisions from his point of view only but collects all ideas from all employees and then conducts deliberations and decides together. It means being an innovative leader is through the leadership style applied by the leader. To win the competition, education providers must at least have a competitive attitude in carrying out their institutional duties. Related to this, leaders need to analyze the needs of students and map the trends and strengths of competition, set quality standards, and formulate demands for environmental needs and trends. The most effective innovative leadership traits are those who clearly describe their vision of the end result of their innovation. They are able to clearly describe their goals, dreams, hopes, and imaginations about the changes they want to achieve. They are able to describe it very well, thus inspiring the people they lead to work harder to make it happen. The competitiveness of madrasas in the context of the current era is an absolute thing. This competitiveness correlates with the quality of the madrasa, the more qualified and professional the management of the madrasa, the more competitive it will be. The Urgency of Improving the Quality and Competitiveness of Madrasas The effective and efficient implementation of education from a madrasa should refer to the complex and ever-changing interests of society from every era. graduate service users.